2018
DOI: 10.1080/09584935.2018.1425673
|View full text |Cite
|
Sign up to set email alerts
|

Social movements and the scaling of memory and justice in Bhopal

Abstract: This paper examines the politics of scale in the commemorative work undertaken by the International Campaign for Justice in Bhopal (ICJB), a coalition of social movement organisations seeking justice for the victims of the Bhopal Gas Disaster of 1984. The argument traces how the ICJB attempted to contest the localisation of the disaster by the Indian state and the transnational corporations involved. I outline how the disaster, which had been scaled down from an extraordinary global event to a private non-issu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Second, research has revealed how environmental justice movements cultivate memories of environmental change in seeking to achieve their objectives. Such bottom-up memory work provides evidence of ‘what happened’ – thereby challenging amnesia and hegemonic narratives (Perreault, 2018) – and gives meaning to environmental pollution and suffering, which may help mobilise support for the movement (Bisht, 2018; Sayers, 2006). Third, a growing body of work investigates how local memories of environmental disasters – ranging from floods (Garde-Hansen et al, 2017) to bushfires (Reid et al, 2018) – facilitate disaster preparation and bolster community resilience.…”
Section: Remembering Environmental Change: the ‘Nonhuman Turn’ In Mem...mentioning
confidence: 99%
“…Second, research has revealed how environmental justice movements cultivate memories of environmental change in seeking to achieve their objectives. Such bottom-up memory work provides evidence of ‘what happened’ – thereby challenging amnesia and hegemonic narratives (Perreault, 2018) – and gives meaning to environmental pollution and suffering, which may help mobilise support for the movement (Bisht, 2018; Sayers, 2006). Third, a growing body of work investigates how local memories of environmental disasters – ranging from floods (Garde-Hansen et al, 2017) to bushfires (Reid et al, 2018) – facilitate disaster preparation and bolster community resilience.…”
Section: Remembering Environmental Change: the ‘Nonhuman Turn’ In Mem...mentioning
confidence: 99%